Demographics and the current account - Joschka Gerigk; Miriam Rinawi; Adrien Wicht (Aussenwirtschaft, 2018)
This paper investigates the relationship between demographics and the current account. We analyze the impact of recent demographic changes and provide a forecast of its future impact. Overall, we find a strong and robust, non-linear demographic effect. In particular, we find a positive association between the current account and the share of a population's prime-age individuals and a negative association with the share of the elderly. Our forecast suggests that, given the dramatically aging population in most industrialized countries, demographics will likely decrease the current account balance in the near future in those countries.
Keywords: F11; F32; F41; 330; demography; aging; current account; savings